2017
DOI: 10.1007/s11764-017-0662-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of chemotherapy-induced neurotoxicities on adult cancer survivors’ symptom burden and quality of life

Abstract: Survivors need to be evaluated for these neurotoxicities and receive appropriate interventions. Referrals to audiologists and physical therapists are warranted to improve survivors' hearing ability, functional status, and QOL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 72 publications
1
58
0
Order By: Relevance
“…Given that the number of cancer survivors in the United States is expected to reach 22.1 million by 2030, an increased emphasis is being placed on the evaluation of persistent adverse effects associated with its treatment . Persistent fatigue, anxiety, depression, pain, sleep disturbance, and cognitive deficits are extremely common, often co‐occur, and result in significant decrements in survivors' functional status and quality of life . Given the growing number of cancer survivors, as well as recent reports of the negative impact of persistent symptoms, a detailed evaluation of the symptom experience of these individuals is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the number of cancer survivors in the United States is expected to reach 22.1 million by 2030, an increased emphasis is being placed on the evaluation of persistent adverse effects associated with its treatment . Persistent fatigue, anxiety, depression, pain, sleep disturbance, and cognitive deficits are extremely common, often co‐occur, and result in significant decrements in survivors' functional status and quality of life . Given the growing number of cancer survivors, as well as recent reports of the negative impact of persistent symptoms, a detailed evaluation of the symptom experience of these individuals is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…As chemotherapeutic drugs were carboplatin, cyclophosphamide and doxorubicin, which can damage permanently organ of hearing as described [3,14,15]. Investigators described that platinnun drugs affected 14% of cancer treatment´s survivors once these drugs are considered not only ototoxic, but neurotoxic [15]. The incidence of hearing loss for head and neck cancer, in our study was 28.8% therefore investigators reported an incidence of 27% to 95% [13].…”
Section: Discussionmentioning
confidence: 49%
“…In our research, all patients received, and 3D radiotherapy as prescribed by oncologist. As chemotherapeutic drugs were carboplatin, cyclophosphamide and doxorubicin, which can damage permanently organ of hearing as described [3,14,15]. Investigators described that platinnun drugs affected 14% of cancer treatment´s survivors once these drugs are considered not only ototoxic, but neurotoxic [15].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations